Deciphering Tour Guides’ English Communicative Competence: Some Evidence from Indonesia - Fuad Abdullah; Arini Nurul Hidayati; Agis Andriani; Soni Tantan Tandiana (Journal of English Language Studies, 2022)
Possessing a well-established English communicative competence (hereafter, ECC) is highly demanding since it can contribute to the production of fluent, accurate, and intelligible communication. Unfortunately, insufficient attention has been addressed to delve into Pangandaran tour guides' English communicative competence. This study aims to delineate the ECC of Pangandaran tour guides in Pangandaran, Indonesia. The data were collected through a focus group discussion consisting of six participants from miscellaneous institutions and were analyzed through Thematic Analysis (Braun and Clarke, 2006). The findings demonstrated that Pangandaran tour guides' ECC were outlined in five descriptions, namely (1) committing recursive grammatical errors while speaking in English, (2) designating insufficient spoken English vocabulary, (3) possessing vast and in-depth prior knowledge about Pangandaran, (4) diagnosing problems and proposing their various solutions and (5) showcasing visionary thoughts towards tourism destination development. Given these facts, ECC enables the tour guides to create sustainable job and business opportunities for themselves, the local people, and the government.Keywords: Communicative competence; English; Indonesian tourism; Pangandaran tour guides